Tracing dissolved organic matter in inflowing rivers of Nansi Lake as a storage reservoir: Implications for water-quality control. (January 2022) - Feng, Likui; Zhang, Jian; Fan, Jinlin; Wei, Liangliang; He, Shufei; Wu, Haiming
Abstract: Quantitative characterization of dissolved organic matter (DOM) in various aquatic ecosystems has become of increasing importance as its transformation plays a key role in inland water carbon, yet few studies have quantified water DOM inputs to storage lakes for water quality control and safety assurance. This study assessed the quantity and quality of DOM in 21 inflow rivers of Nansi Lake as the important storage lake of large-scale water transfer projects by using excitation-emission matrix spectroscopy coupled with parallel factor analysis (EEM-PARAFAC) and ultraviolet–visible (UV–Vis) spectroscopy. The results showed that DOM contents varied significantly with an average value of 5.8 mg L −1 in different inflow rivers, and three fluorescence substances (including UVC humic-like, UVA humic-like and tyrosine-like components) were identified by EEM-PARAFAC. The distribution of the DOM components was distinctively different among sampling sites, and UVA humic-like component mainly dominated in Nansi Lake. Meanwhile, DOM components with higher aromaticity and molecular weight were found in the west side of lake. Fluorescence spectral indexes manifested that the source of DOM was mainly from allochthonous or terrestrial input. Moreover, significant correlations between water quality and DOM characteristics were observed in Nansi Lake. These findings would be beneficial to understand the biogeochemical role and impact of DOM in inflowing rivers in the water-quality monitoring and control of storage lakes. Graphical abstract: Image 1 Highlights: Three fluorescent components were found in DOM in inflowing rivers of Nansi Lake. Distribution of DOM components was distinctively different among sampling sites. Allochthonous or terrestrial input was the main source of DOM in Nansi Lake. Significant correlations were observed between DOM and water quality indexes.